Coordinated SPD Systems for Mitigating the Effect of Lightning-Induced Voltage on Hybrid Solar PV-Battery Energy Storage System - Ahmad N.I.; Ab Kadir M.Z.A.; Ali Z.; Osman M.; Roslan M.H.; Zaini N.H. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper discusses the effect of lightning-induced voltage on a hybrid solar photovoltaic (PV)-battery energy storage system (BESS) without an external lightning protection system (LPS). Solar PV generates electricity by converting solar energy and providing it to the user. In addition, battery energy storage is also utilised to supply consistency and satisfy the need for energy. However, because the system is installed in open spaces, lightning has always been a huge difficulty for it to work at optimal efficiency. In this paper, the single SPD Class I was installed near the inverter on the DC side. The study on cable length with various lightning current amplitude and lightning strike distance is conducted. The simulation findings found that the inverter is well protected by the SPD whereby the impulse withstand voltage is 6 kV, however, the solar PV-BESS is affected by the lightning-induced voltage regardless of any cable length. In this way, providing the requirement for an adequate SPD installation will ensure improved maintenance and extend the equipment's lifespan. 2023 IEEE.